Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
y-(12*x^2-9*x+4)=0
Step by step solution :<span>Step 1 :</span><span>Equation at the end of step 1 :</span><span> y - (((22•3x2) - 9x) + 4) = 0
</span><span>Step 2 :</span><span>Equation at the end of step 2 :</span><span> y - 12x2 + 9x - 4 = 0
</span><span>Step 3 :</span>Solving a Single Variable Equation :
<span> 3.1 </span> Solve <span> <span>y-12x2+9x-4</span> </span> = 0
In this type of equations, having more than one variable (unknown), you have to specify for which variable you want the equation solved.
Answer:
466 student
Step-by-step explanation:
The number of students that like at most 2 kinds of these chocolate candies can be gotten from subtracting the number of students that like more than 2 candies from the total number of high school students.
Since 34 like all three kinds of chocolate candy, hence:
Number of students that like at most 2 kinds of these chocolate candies = 500 - 34 = 466
466 students like at most 2 kinds of these chocolate candies
Answer:
Step-by-step explanation:
The max value that this function reaches is 6, and the function reaches this value repeatedly, beginning at x = 0 and then at x = 6, 12, 15, etc. This tells us that the period of the function is 6.
The function is increasing on (3, 6), (9, 12), and so on
The function is even because the graph is symmetrical about the y-axis.
The solutions of the equations are x = 1 and y = 2
The system of equations are
4x + 3y = 10
-4x + 5y = 6
Here we have to use the elimination method. Eliminate the x term and find the value of y term
Add both equation
3y + 5y = 10 +6
Add the like terms
8y = 16
y = 16 / 8
Divide the terms
y = 2
Substitute the value of x in the first equation
4x + 3y = 10
4x + 3×2 = 10
Multiply the terms
4x + 6 = 10
4x = 10 - 6
4x = 4
x = 4 / 4
Divide the terms
x = 1
Hence, the solutions of the equations are x = 1 and y = 2
Learn more about elimination method here
brainly.com/question/14619835
#SPJ1